Peran Public relations dalam Membangun Ekuitas Merek Mobil Listrik Wuling Air EV di Indonesia - Ceicilia Ceicilia; Dewi Sri; Mohamad Zein Saleh (Jurnal Kendali Teknik dan Sains, 2024)
This research employs a quantitative research methods to analyze the important role of Public relations (PR) in building brand equity and the existence of Wuling Air EV electric car products in Indonesia. In an era that increasingly emphasizes environmental issues, the automotive industry is turning to environmentally friendly vehicles such as electric cars. Wuling, as a newcomer in this market, faces challenges in building consumer trust and competing with established brands. Through effective PR strategies, such as media relations, digital campaigns, and active participation in social media, Wuling strives to increase brand awareness, positive image, and customer loyalty. With a focus on educating consumers about the benefits of electric vehicles, Wuling Air EV is expected to maintain and strengthen its position in the competitive automotive market.